Contaminations removal from static lake water by compound - 刘书宇 吴明红 马放 张杰 顾晓婧 (Journal of Shanghai University, 2010)
Urban wastewater treatment techniques could not be applied to improve the pollutant removal efficiency,due to its characteristics of closed and quiescent conditions of the static lake water.In this study,natural zeolite and coal cinder were chosen as filler compounds of the ecological filter.Static and dynamic experiments were carried out to study the remediation efficiency.Experimental data show that removal efficiency of ammonia nitrogen （NH ＋ 4 -N） reaches 85% in both static and dynamic patterns and its removal efficiency reaches 97% when the recycling period is 1 h in dynamic condition.The maximum removal efficiency of nitrite nitrogen （NO-2 -N） reached 98%,and the removal efficiency of total nitrogen （TN） is a maximum of 84%.The final effluent concentration of total phosphorus （TP） is 0.079 mg/L.Effluent recycling could improve the nutrient （N,P） removal efficiently.Dissolved oxygen （DO） concentration could remain high with the water cycling.The filter works efficiently on regulating pH to the standard level of healthy water.